Carbon stock and diversity of Pagatban Mangrove Forest in Bayawan, Negros Oriental - Carreon, Jose Carlo Miguel G. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Mangrove forests provide many ecosystem services and serve as major carbon sinks. In the Philippines, total mangrove cover decreased from 500,000 ha in 1918 to 120,500 ha in 1994. Conducting mangrove carbon stock assessments is relevant in management intervention and conservation efforts to highlight the significance of mangrove forests in climate change mitigation. This study assessed the carbon stock and diversity of the Pagatban mangrove forest in Bayawan City, Negros Oriental. Conducting a carbon stock assessment in the area will provide preliminary data for carbon neutrality plans by the local government. The transect line plot method was used to sample the entire forest, with 17 plots of 10 x 10 meters. Species identification and measurement of stem diameter at breast height (dbâ„Ž) were done for each tree. Carbon stock was obtained using allometric equations. Shannon-Wiener Diversity Index (H') and Importance value index (IVI) were used to measure diversity and determine the most dominant species, respectively. A total of 418 mangrove trees were sampled wherein R. stylosa is the most dominant species (IVI = 129.6). The diversity in the Pagatban mangrove forest is low (H' = 0.67) compared to other mangrove forest in the Philippines. It is estimated that the total biomass/ha is 243,184.4 kg equivalent to a total of 114,296.6 kg of carbon and 419,468.7 kg of CO2 sequestered per hectare. These values are below the averages for Philippine mangrove forests. However, despite the low diversity and below-average carbon stock, the Pagatban mangrove forest still sequesters relevant amounts of carbon. It is also predicted that the Pagatban mangrove forest will sequester 25,638,626 kg of CO2 by 2050 and will accumulate 600,674 kg/ha of biomass by 2030, surpassing the average values for Philippine mangrove forests. This assessment of the Pagatban mangrove forest provides preliminary data for diversity, biomass, carbon stock, and future predictions.